Academic musings on globalisation and ‘local’ relevancy: a step in the right direction? - Vejai Balasubramaniam, (Universiti Kebangsaan Malaysia, 2003)
In the post Cold War epoch the issue of globalisation has attracted much attention from academics in the Third World. Of particular concern is the impact of globalisation on labour and job opportunities. In this respect high unemployment among social science graduates from public institutes of higher education in Malaysia has brought to the forefront the question of relevancy of courses taught there. Yet the view that globalization and international competitiveness may compromise the context of the social sciences may be misplaced. This paper discusses the issues of concern and asks whether it is social science or social scientists who are at stake.